Validation and measurement invariance of the Arabic Health Literacy Questionnaire - Jehad A. Rababah; Mohammed M. Al-Hammouri; Mohammed Aldalaykeh (Heliyon, 2022)
Health literacy plays a key role in empowering individuals and enabling them to make health-related decisions. Despite the advances in health literacy research, there are gaps in the literature that require further inquiry, and establishing comprehensive and valid measurements is one of them. Thus, this research was conducted to examine the psychometric properties of the Arabic Health Literacy Questionnaire (HLQ), including the reliability, validity, and measurement invariances of the nine HLQ scales. A cross-sectional design was used in this study. A sample of university students (N = 1011) was recruited, the mean of age was 21.1 years old (SD = 2.28). The Arabic HLQ and a demographics questionnaire were completed by the participants. Confirmatory factor analyses (CFA) and measurement invariances were performed for each HLQ scale. The values of Cronbach's α and composite reliability were above .70 for all HLQ scales. The CFA analyses showed that all HLQ scales meet the criteria that were set a priori: RMSEA ≤.07, CFI ≥.95, and Chisq/df < 5. In addition, all standardized factor loadings were above .50. Regarding the measurement invariance, the results supported the equal form measurement invariance for all HLQ scales. The equality of factor loadings measurement invariance across gender was also supported for all HLQ scales. Measurement invariance of factor loadings and equality of indicator intercepts was partially supported. These results show that the internal consistency, convergence, and factor structure of the HLQ are all supported. The Arabic HLQ is a reliable, valid tool to measure health literacy among Arabic-speaking populations.